THE SOCIAL-PHILOSOPHICAL CONSEPT OF MEDIA (Symposium on Natural and Applied Sciences, 2026)
In todayʼs rapidly developing information and communication technologies, modern media are emerging as a powerful mechanism for the development of not only the stateʼs means of disseminating information, but also the economic, social, political and cultural spheres of society. The research paper analyzes the views and theories related to the origin of the media, the tasks of the media in a democratic society, the factors that have a positive and negative impact on the development of the media space, the role and importance of the media in the development of society. Based on the results of the analysis, practical recommendations have been developed to ensure freedom of information in society, ensure the legal and professional immunity of the media and media workers, and increase the media literacy of the population.The article is recommended for use as a methodological guide by students, teachers, and researchers working in the field of media and journalism.
Keywords: Media, mass media, society, media literacy, media content, internet, television, digitization, e-government, journalist, blogger, newspaper, magazine.